The effective of health communication about the awareness of COVID-19 through social media - Andaleep Sadi Ades (Social Medicine Publication Group, 2021)
The on-going pandemic of COVID-19 has threatened the lives of all the populations across the world as everything, ranging from economic to social have since come into a standstill. Social media such as twitter has been used more frequently to disseminate essential information regarding the pandemic. This study aim to explore if social media or mass media are relied on when seeking information about COVID-19, and subsequently establish the effectiveness of using social media as a health communication tool to create awareness of COVID-19 among members of the public. The researcher adopted a cross-sectional study design in which 500 questionnaires were distributed and filled via survey monkey. The overall findings have shown that people used social media more than mass media in seeking information about COVID-19. Twitter handles as well as other digital social media platforms such as Facebook are effective means of communication in the contemporary society and can, therefore, be effectively and efficiently used by healthcare organizations and various government institutions to create awareness on how to control the pandemic through hand washing, wearing of face mask, and keeping social distance. The paper has ended by recommending aspects for future studies on the same topic.